mRNA EXPRESSION OF PD-1, PD-L1, AND IMMUNOTHERAPY IN BLADDER CANCER - Mauny, Muhammad Puteh; Raden Danarto; Heriyanto, Didik Setyo (Indonesian Urological Association, 2021)
Objective: This study aims to investigate mRNA expression of PD-1 and PD-L1 in patients with bladder cancer. Material & Methods: In this study, we examined 30 samples from paraffin embedded tissue blocks, samples were divided into two groups, 15 were NIMBC, and 15 were MIBC according to their histopathological result. mRNA expression of PD-1 and PD-L1 were conducted using Real Time-Polymerase Chain Reaction (qRT-PCR) and statistical significance was set at a p-value < 0.05. Results: Statistical analysis using the Mann-Whitney test found a significant difference in mRNA expression of PD-1 and PD-L1 in NMIBC compared to MIBC groups. Conclusion: mRNA expression of PD-1 and PD-L1 were higher in MIBC compared to NMIBC. PD-1 and PD-L1 as immune checkpoints are potential immunotherapy for patients with advance stage bladder cancer. Immunotherapy could be a substitute or combined with other treatments such as chemotherapy or radiotherapy.